2022
DOI: 10.54905/disssi/v26i130/ms518e2611
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of ocular complications associated with the use of cosmetic contact lenses from unlicensed vendors among Taif city, Saudi Arabia

Abstract: Background: The usage of CLs has grown significantly and it is only expected to grow. However, CLs' wearers may have risk of eye infections if they fail to wear, clean, disinfect and store their CLs as directed. To assess awareness of ocular complications associated with the use of cosmetic contact lenses from unlicensed vendors and its correlation with age, gender and education level among Taif city, Saudi Arabia. Methods: Cross sectional study conducted on the general population of Taif City, Saudi Arabia. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
0
0
Order By: Relevance
“…These results indicate that participants' knowledge about CL's exists but there is lack of awareness and compliance which coincides withDumbleton et al, (2011).Dumbleton et al, (2011) reported that despite 95% of the participants obtained their CL from professional optometrist still the rate of noncompliance is more than expected. Furthermore, another study done on medical student study revealed that despite having the resources and knowledge still they lack the proper compliance on CLs hygienic practices(Ibrahim et al, 2018;Alghamdi et al, 2022). Most of the present work's participants (85.3%) always wash hands before putting on lenses but only (37.9%) always wash their hand with soap and water prior to touching the lenses.…”
mentioning
confidence: 76%
“…These results indicate that participants' knowledge about CL's exists but there is lack of awareness and compliance which coincides withDumbleton et al, (2011).Dumbleton et al, (2011) reported that despite 95% of the participants obtained their CL from professional optometrist still the rate of noncompliance is more than expected. Furthermore, another study done on medical student study revealed that despite having the resources and knowledge still they lack the proper compliance on CLs hygienic practices(Ibrahim et al, 2018;Alghamdi et al, 2022). Most of the present work's participants (85.3%) always wash hands before putting on lenses but only (37.9%) always wash their hand with soap and water prior to touching the lenses.…”
mentioning
confidence: 76%